Hemophilia A and hemophilia B: focus on arthropathy and variables affecting bleeding severity and prophylaxis. Issue 8 (14th August 2013) - Escobar, M.; Sallah, S.
Summary Hemophilia A (HA) and hemophilia B (HB) are X‐linked, recessive disorders. Although their clinical manifestations are essentially indistinguishable, it has been suggested that bleeding episodes in patients with HA are generally more severe and occur at higher frequency than in patients with HB. Nevertheless, considerable debate remains regarding the relative severity of HA and HB. Based on the relative risk of undergoing joint arthroplasty, it appears that patients with HA have more severe joint deterioration compared with patients with HB. Although it is difficult to speculate on the factors that might modify bleeding severity in patients with hemophilia, recent observations indicate that other coagulation proteins, such as tissue factor pathway inhibitor or polymorphisms in coagulation factor genes and genetic defects associated with hypercoagulability may account for the variability in clinical phenotype among patients with hemophilia. Numerous studies have provided evidence supporting the clinical and social benefits of administration of clotting factor in prophylaxis. However, it is still unclear why this approach is more commonly utilized in patients with HA than in those with HB.